To Assess And Compare The Operational And Financial Performance Of Stand-Alone Restaurants In Kolkata ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2021)
Background: Nowadays, numerous restaurants have started operating with different and creative  ideas. Apart from the chains and traditional brands of restaurants, the stand-alone variety is  also emerging with modern concepts. The analysis and comparison of the performance of these  stand-alone restaurants will provide insights into the market for such outlets. Objectives:  The study assesses and compares the performance of stand-alone restaurants based on their  operations and financial management. Methodology: The study has been carried out on two  restaurants located in busy areas of Kolkata, West Bengal, India. The tools used for primary  data collection are in-depth interviews with the restaurant owners, consolidated with the  restaurant’s financial data. Analytical design was adopted and mathematical tool for data  comparison was used. Results: It was observed that Restaurant Y performed better than  Restaurant X, securing an average profit percent of 14.37% over 17 months. The other suffered  an average loss of 10.28% during the same period. Patterns emerged indicating that revenue  peaked during the months of September and October. Conclusion: Restaurant profiles, seating  area, type of cuisine, value proposition alignment, cost structure, inventory, staff, and ticket  price are important factors for a restaurant’s success. Customer sentiments impact the market,  while Bengal’s Durga Puja is a driver for high revenue for such restaurants.
Keywords: Stand-alone Restaurants; Analysis; Comparison; Financial position; Performance; Trends